Health Infrastructure Service Management Using Nonlinear Pushover Analysis Based on Earthquake Response Spectrum - Paikun; Nelfia, Lisa; Suhendi, Cece; Aulia, Riza; Dunu, Williams (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
This study aims to determine the inter-floor shift due to earthquake spectrum response using nonlinear pushover analysis in a clinic building located in the Cimandiri Fault Zone as a basis for healthcare infrastructure management. This is very important because healthcare infrastructure is a place that must be available in any condition, even after an earthquake disaster. The Sukabumi area is an area located in the Cimandiri Fault Zone, so buildings in this area must be specifically designed to remain intact during disasters, especially earthquakes that often cause building damage. The research object that is the case study in this study is a 4-story clinic building that uses a reinforced concrete structure. The method used in the earthquake spectrum response analysis refers to SNI 1726:2019 and SNI 2847:2019, which have available spectral response webs, while the nonlinear pushover analysis uses the ATC-40 and FEMA-440 methods implemented in ETABS. The results of the analysis show that the inter-floor shift on the second and third floors exceeds the specified service limits, so it can be stated that the clinic building structure service in this case study requires damage control (DO). This can be seen based on the analysis results that the inter-floor shift of 201 mm in the X direction and 190 mm in the Y direction can cause moderate damage that can be repaired, so that health infrastructure service management is very necessary. Controlling recurrent damage due to earthquakes can be done with three retrofit scenarios consisting of the addition of shear walls, column coating, and steel reinforcement. The three scenarios are assessed and ranked based on the reduction of shifts, repair duration, and functional disruption. The addition of shear walls is the main recommendation without disrupting functionality, while column coating and the addition of steel reinforcement can disrupt health service operations. Retrofit scenarios can be recommended to support a sustainable health service infrastructure system in earthquake-prone areas. Earthquake spectrum response is a key factor that needs to be reviewed in building damage analysis as a basis for risk control management of health service infrastructure.